Precision Analysis of Chinese VLBI Network Software Correlator for Geodetic Applications - LIU Lei (Acta Geodaetica et Cartographica Sinica, 2017)
To support international VLBI geodetic data processing, Chinese VLBI Network (CVN) software correlator has been updated for better performance and more features, including geodetic Mk4 data format output and improvement of signal to noise ratios. After updating, the visibility output of the software correlator can be sent to the standard VLBI geodetic postprocessing software to derive observables. To verify the correlation result, we have carried out correlation with both CVN software correlator and the popular DiFX correlator by using the same data set. We have compared the derived multi-band residual delay/rate, total delay/rate, signal to noise ratio, and the solved VLBI site positions. The comparison results demonstrate that the CVN software correlator has achieved the required precision, and therefore it can be used for IVS geodetic data processing.